2019
DOI: 10.1021/acsami.9b07865
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Doping-Site-Variation-Induced Composite Cathode Adjustment: A Case Study of Layer–Tunnel Na0.6MnO2 with Mg2+ Doping at Na/Mn Site

Abstract: Composite cathodes have attracted great attention due to the integrated advantages of each pure structure. Also, the component ratio deserves a careful modulation to further improve the corresponding electrochemical performance. Mn-based layer–tunnel hybrid composite became a focus in sodium-ion batteries due to the superiority in terms of high performance, low cost, and nontoxicity. In the previous reports, the structure modulation was carried out via changing the synthesis condition, varying the transition-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The XRD peaks of all samples are consistent with the P2-type triangular prism structure with the P6 3 /mmc space group (No 194). ,, As presented in Figure b, the (002) peaks shift toward the lower angle as a result of multielement substitution. The left shift of the (002) peak indicates the increase of the cell parameter c value, which is conducive to the enlargement of Na layer spacing. ,, The atom occupancy of bare-MF, MFCa, MFMg, and MFCaMg from Rietveld refinement has been shown in Tables S1–S4. The doped atoms have been introduced into the designed lattice sites successfully. In addition, the XRD refinement results have been applied to reconstruct the crystal structure of all four samples, as provided in Figure a–d.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The XRD peaks of all samples are consistent with the P2-type triangular prism structure with the P6 3 /mmc space group (No 194). ,, As presented in Figure b, the (002) peaks shift toward the lower angle as a result of multielement substitution. The left shift of the (002) peak indicates the increase of the cell parameter c value, which is conducive to the enlargement of Na layer spacing. ,, The atom occupancy of bare-MF, MFCa, MFMg, and MFCaMg from Rietveld refinement has been shown in Tables S1–S4. The doped atoms have been introduced into the designed lattice sites successfully. In addition, the XRD refinement results have been applied to reconstruct the crystal structure of all four samples, as provided in Figure a–d.…”
Section: Resultsmentioning
confidence: 99%
“…The left shift of the (002) peak indicates the increase of the cell parameter c value, which is conducive to the enlargement of Na layer spacing. 41,48,50 The atom occupancy of bare-MF, MFCa, MFMg, and MFCaMg from Rietveld refinement has been shown in Tables S1−S4. The doped atoms have been introduced into the designed lattice sites successfully.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase transition was observed for the undoped oxide from a series of ex situ X-ray diffraction (XRD) patterns upon charging, while the Mg-doped sample still preserved the P2 structure. It was further confirmed that regardless of the occupancies of Mg 2+ at the transition-metal sites or Na sites, the undesirable P2–O2 phase transition can be clearly suppressed, leading to superior cycling stability . Nevertheless, the effects of Mg 2+ doping on the material and electrochemical properties of NVPF have not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It was further confirmed that regardless of the occupancies of Mg 2+ at the transition-metal sites or Na sites, the undesirable P2−O2 phase transition can be clearly suppressed, leading to superior cycling stability. 29 Nevertheless, the effects of Mg 2+ doping on the material and electrochemical properties of NVPF have not yet been explored. This study will thus address this issue.…”
Section: ■ Introductionmentioning
confidence: 99%